2006
DOI: 10.1186/1745-6673-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the causes of chronic cough: relation to diesel exhaust, ozone, nitrogen oxides, sulphur oxides and other environmental factors

Abstract: Air pollution remains a leading cause of many respiratory diseases including chronic cough. Although episodes of incidental, dramatic air pollution are relatively rare, current levels of exposure of pollutants in industrialized and developing countries such as total articles, diesel exhaust particles and common cigarette smoke may be responsible for the development of chronic cough both in children and adults. The present study analyses the effects of common environmental factors as potential causes of chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 88 publications
1
19
0
Order By: Relevance
“…We consider that the respiratory disease in this group was caused mainly by the high environmental levels of SO 2 and NO 2 during 1965 to 1974, because approximately 60% of the victims were first registered during the 1970s. Our results are consistent with those of past reports indicating that high environmental levels of SO 2 (40–60 ppb) and NO 2 (17.4 ppb) can affect the bronchi and bronchioles, resulting in respiratory symptoms such as a cough, sputum, wheeze, and breathlessness [1-7,15-17]. Our results show significant differences in respiratory function between males and females at the time of certification, with FEV 1 % predicted, FVC % predicted, VC % predicted, and FEV 1 /FVC (%) significantly lower in males than in females.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We consider that the respiratory disease in this group was caused mainly by the high environmental levels of SO 2 and NO 2 during 1965 to 1974, because approximately 60% of the victims were first registered during the 1970s. Our results are consistent with those of past reports indicating that high environmental levels of SO 2 (40–60 ppb) and NO 2 (17.4 ppb) can affect the bronchi and bronchioles, resulting in respiratory symptoms such as a cough, sputum, wheeze, and breathlessness [1-7,15-17]. Our results show significant differences in respiratory function between males and females at the time of certification, with FEV 1 % predicted, FVC % predicted, VC % predicted, and FEV 1 /FVC (%) significantly lower in males than in females.…”
Section: Discussionsupporting
confidence: 93%
“…Epidemiological studies have reported that air pollution is associated with adverse respiratory effects [1-7] and increased mortality [8-10]. Some areas of Japan experienced high levels of air pollution during the period of rapid economic growth after World War II and many people who lived in these areas complained about respiratory symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to environmental irritants, including ambient pollutants known to trigger cough both in children and adults, has been reviewed [8,9,10]. In addition, there is evidence from cross-sectional studies that have shown the association in adults [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Infections of the pharynx and upper respiratory tract are common conditions that may initiate exacerbations of bronchial asthma [1], chronic obstructive pulmonary disease (COPD) [1, 2] or occupational and environmental airway diseases [3,4,5,6,7]. Especially in patients with moderate to severe stages, such as GINA stage 3–4 for bronchial asthma or GOLD stage 3–4 for COPD, these infections can cause severe damages to the respiratory tract and may lead to hospital admission [8].…”
Section: Introductionmentioning
confidence: 99%